Protein abundance alterations in matched sets of macroscopically normal colon mucosa and colorectal carcinoma - Stulík, J; Koupilova, K; Osterreicher, J; Knízek, J; Macela, A; Bures, J; Jandík, P; Langr, F; Dedic, K; Jungblut, P R (Electrophoresis, 1999)
Our current results, aimed at the detection of protein abundance alterations that could be associated with the process of colon tumorigenesis, are summarized. The matched sets of macroscopically normal colon mucosa and colorectal carcinoma were examined by a one- or two-dimensional electrophoretic approach and proteins were identified using immunoblotting or mass spectrometry. The following results were observed: The levels of liver fatty acid-binding protein, actin-binding protein/smooth muscle protein 22-alpha and cyclooxygenase 2 were downregulated in colorectal carcinoma compared to normal colon mucosa. Conversely, the expression of a novel variant of heat shock protein70 and several members of the S100 protein family of calcium-binding proteins (two isoforms of S100A9, S100A8, S100A11 and S100A6) were upregulated in transformed colon mucosa. Despite the variations of the levels of expression of given protein among analyzed samples, all quantitative changes were found to be statistically significant (Mann-Whitney test assuming p < or = 0.05). We conclude that the proteomic approach is useful for the study of complex biological events underlying the process of colorectal tumorigenesis.
Keywords: Electrophoresis, Polyacrylamide Gel; protein - isoformy; střevní sliznice; Protein Isoforms; kolon; Humans; S100 Proteins; kolorektální nádory; Colon; lidé; elektroforéza v polyakrylamidovém gelu; Intestinal Mucosa; Colorectal Neoplasms; proteiny S100